Komunikasi Interprofesional sebagai Faktor Penentu Kinerja Tugas Tim - Angelia Putriana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Interprofessional communication is a key component in supporting team task performance and ensuring patient safety in healthcare settings. This study aims to analyze the role of interprofessional communication as a determining factor of team task performance within the context of healthcare simulation. A prospective observational approach was employed, involving final-year nursing students who worked in small teams during emergency simulation scenarios. Team task performance was assessed across two phases: the initial phase prior to communication with a physician and the subsequent phase following the receipt of verbal instructions. Interprofessional communication was evaluated using a structured communication framework and an instruction confirmation mechanism. The findings indicate that teams demonstrating higher-quality communication tended to achieve more consistent and higher levels of task performance. Approximately 94–100% of teams were able to conduct basic patient assessments effectively; however, only 18% performed priority early interventions promptly. Following verbal instructions, the implementation of routine clinical actions increased to 88–92%, while the execution of more complex actions remained relatively low. These results underscore that structured interprofessional communication, combined with effective instruction confirmation, plays a critical role in enhancing the accuracy, consistency, and overall effectiveness of team task performance in healthcare environments.